The Impact of the Financial Wellbeing of the Elderly of Kazakhstan on Their Family Life - Z. T. Satpayeva; A. S. Bekbossinova; M. M. Ryskulova (Экономика: стратегия и практика, 2021)
Today, many countries in the world are concerned about the well-being of pensioners, as their number is growing every year and pension systems cannot cope with ensuring a decent old age. The well-being of pensioners is part of the well-being of society, and the pension system is an institution for ensuring the well-being of pensioners. Therefore, it is important to understand the relationship between the financial well-being of older people and the country’s pension system. It is also important to understand that the family is an integral part of a person and therefore the well-being of each family member affects family relationships. This article is devoted to the assessment of the financial well-being of pensioners in Kazakhstan as a key factor affecting the family relations of a pensioner with partner, children, and grandchildren. Primary and secondary data were used for this study. The primary data were collected through interviews, which allowed us to obtain a subjective definition of financial well-being on the part of pensioners and its impact on family relations. This data was processed and encoded using the Atlas.ti program. Data from the Bureau of National Statistics made it possible to objectively assess the financial situation of Kazakhstani pensioners. The study found that the concept of financial well-being among Kazakhstani pensioners is more important for men than for women. Pensioners are not happy with their financial well-being, but this does not significantly affect their relationship with their families. The results of the study will allow us to assess the financial well-being of pensioners and can be used in the reform of social policy, pension provision of the country. Through the use of interviews financial literacy has been identified as one of the key factors, which depends on circumstances and the context.